The Role of Managerial Coaching on Performance: Mediating Analysis of Employee Psychological Capital - Novitasari, Dewiana (IJOSMAS, 2021)
This study aims to examine the effect of managerial coaching on performance and to investigate the mediating effect of psychological capital on the employee population of a manufacturing company in Tangerang, Indonesia. This study adopted the simple random sampling method with 224 employees as samples. The result of this study indicate that managerial coaching has a significant effect on employee performance. The results also show that the relationship between managerial coaching and performance is significantly mediated by the psychological capital. This research can pave the way to improve employee readiness in the face of in the industrial revolution 4.0 era